Nanoantenna : plasmon-enhanced spectroscopies for biotechnological applications - Lamy de la Chapelle, Marc; Pucci, Annemarie (Pan Stanford series on the high-tech of biotechnology, 2013)
This book concentrates on the various fields related to the development of a nanobiosensor and presents the latest information from renowned experts. It focuses on the enhanced spectroscopy, including SERS, SEIRA/SEIRS, and near-field optics, and the related physical processes (optical properties of metallic nanoparticles, plasmon resonance, field enhancement, etc.). Some applications in the biological and medical field are presented to show the potential of such techniques as sensors if combined with functionalization.